New York, Bookworms 2 - Escott, John. (New York Oxford University Press, 1995)
New York The Big Apple. The history of the city and some of the things you can see and do there today the skyscrapers and the subway, the shops and the sports, the museums and the restaurants and the people themselves. All the things that make New York the most exciting cite in the world.
Keywords: English Grammar